The Nexus of FTFs Counterterrorism Strategy, Immigration Control, and Border Security Through Indonesia's Migration Policy - Yanos Okterano; Heru Susetyo (Jurnal Ilmiah Kebijakan Hukum, 2025)
This study employs a single case study to build an initial understanding of a case or an evaluation of a fatal attack by Uzbekistan detainees affiliated with a terrorist group to the immigration office at the North Jakarta Immigration Office. This work aims to design a counterterrorism strategy through migration policy and border control in Indonesia after the COVID-19 pandemic to build the resilience of nations to fight against radicalism and extremism. It finds that an immigration clearance process in border control management to prevent FTFs from entering Indonesia is limited to administrative clearance and a repository system of their documents and biometric data. Counterterrorism at immigration border controls in Indonesia focuses only on a downstream framework or at the stay-reside phase rather than an upstream prevention strategy. We recommend a revision of the Indonesian Immigration Law, which can include an FTFs counterterrorism strategy at immigration border controls. Immigration border control management should always prioritize pre- empting measures with risk management and focus on a pre-arrival interdiction or upstream prevention strategy.